Viral infection in placenta relevant cells – a morphological and immunohistochemical cell culture study. Issue 1 (22nd September 2014) - Turowski, Gitta; Rollag, Halvor; Roald, Borghild
<x xml:space="preserve">Abstract</x> Viral infections in pregnancy are known to cause fetal malformation, growth restriction, and even fetal death. Macroscopic placental examination usually shows slight and unspecific changes. Histology may show secondary, non‐specific tissue reaction, i.e. villitis with lymphocytic invasion. Primary specific morphology characteristics are known for some virus, like cytomegalovirus, parvovirus, and herpes simplex, however many viral infections show non‐specific changes. Placenta relevant cells as human first trimester trophoblasts HTR8/SVneo, primary human umbilical vein endothelial cells (HUVEC), and primary human embryonic fibroblasts were examined following infection with commonly occurring virus like adenovirus and enterovirus. Morphology in routine stained sections and virus‐specific immunostains were studied 4, 8, 24, 48, 72 h after infection. Nuclear enlargement was seen in the infected cells. A specific diagnosis of adenovirus or enterovirus infection, however, was not possible without specific immunostains.